Exploring the Veterinary Literature: A Bibliometric Methodology for Identifying Interdisciplinary and Collaborative Publications - Hamel, Barbara J.; Moberly, Heather K.; Page, Jessica R.; Youngen, Gregory K. (My University, 2013)
Veterinary medical research traditionally focuses on animal health and wellness; however, research activities at veterinary colleges extend beyond these traditional areas. In this study, we analyzed eleven years of Web of Knowledge-indexed peer-reviewed articles from researchers at the twenty-eight United States American Veterinary Medical Association (AVMA) accredited veterinary colleges. We had three goals in assessing the published literature of veterinary college researchers. First, we identified a list of journals and research areas outside of veterinary medicine in which veterinary researchers publish. This list of journals can be customized to identify those most essential at each institution. Second, we identified collaborative work by veterinary researchers across disciplines and institutions. Using textual analysis tools and visualizations helped us illustrate and clarify this data. Lastly, we developed a methodology for defining an interdisciplinary serials list outside a subject core that can be customized for specific institutions and subject areas.
Keywords: veterinary medicine; journal literature; bibliometrics